Quantitative macroscopic study on preterm placenta in gestational diabetes mellitus and pregnancy induced hypertension (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 280-286 The abstract of this article is available on the PubMed website